2006
DOI: 10.1017/s0025315406013865
|View full text |Cite
|
Sign up to set email alerts
|

Food and feeding ecology of the striped dolphin, Stenella coeruleoalba, in the oceanic waters of the north-east Atlantic

Abstract: The food and feeding ecology of the striped dolphin, Stenella coeruleoalba, in the oceanic waters of the north-east Atlantic were studied using the stomach contents of 60 striped dolphins caught in the albacore drift-net fishery throughout the summer months of 1992 and 1993 off the Bay of Biscay. Thirty-eight per cent of these dolphins were calves (0–1 years old), 25% were juveniles (2–8) and 37% were mature adults (9–32, of which 7 females and 14 males). The diet was found to be primarily composed of fish (39… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 8 publications
(8 reference statements)
3
35
0
Order By: Relevance
“…The diet of the striped dolphin consists primarily of a wide variety of small, midwater and pelagic or benthopelagic fish, especially lantern fish, cod, and squid (Würtz and Marrale 1993, Hassani et al 1997, Archer 2002. In the Mediterranean, striped dolphins are associated with highly productive, oceanic waters beyond the continental shelf (Notarbartolo di Sciara et al 1993, Pulcini et al 1993, Blanco et al 1995, Gannier 2005, where they seem to prey primarily on cephalopods (50-100% of stomach contents), while in the northeastern Atlantic, they most often prey on fish, frequently cod (Archer and Perrin 1999; but also see Ringelstein et al 2006). In the stomach contents of striped dolphins stranded on the Mediterranean coasts of France, Spain, and Italy, Blanco et al (1995) found that the cephalopods Albraliopsis pfefferi, Onychoteuthis banksii, Todarodes sagittatus, and Brachioteuthis riisei were dominant in the western Mediterranean.…”
Section: Discussionmentioning
confidence: 99%
“…The diet of the striped dolphin consists primarily of a wide variety of small, midwater and pelagic or benthopelagic fish, especially lantern fish, cod, and squid (Würtz and Marrale 1993, Hassani et al 1997, Archer 2002. In the Mediterranean, striped dolphins are associated with highly productive, oceanic waters beyond the continental shelf (Notarbartolo di Sciara et al 1993, Pulcini et al 1993, Blanco et al 1995, Gannier 2005, where they seem to prey primarily on cephalopods (50-100% of stomach contents), while in the northeastern Atlantic, they most often prey on fish, frequently cod (Archer and Perrin 1999; but also see Ringelstein et al 2006). In the stomach contents of striped dolphins stranded on the Mediterranean coasts of France, Spain, and Italy, Blanco et al (1995) found that the cephalopods Albraliopsis pfefferi, Onychoteuthis banksii, Todarodes sagittatus, and Brachioteuthis riisei were dominant in the western Mediterranean.…”
Section: Discussionmentioning
confidence: 99%
“…Other delphinid species have been found to be able to forage both in neritic and in oceanic areas. In the Bay of Biscay, the striped dolphin is mainly observed in the oceanic area where it preys on the small migrating mesopelagic fauna (Ringelstein et al 2006), as does the common dolphin. However, the species is sometimes found on the continental shelf of the Bay of Biscay where it consumes essentially small demersal fish.…”
Section: Foraging Behaviormentioning
confidence: 99%
“…Differences in the diet of male and female striped dolphins have been found in the northeast Atlantic, where the female diet is comprised of a number of nonmyctophid fish families and males appear to focus their foraging on myctophids and a few other families (Ringelstein et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…Differences in diet between the sexes have been noted for striped dolphins (Ringelstein et al . ) and other delphinid species. Bottlenose dolphins off the coast of Florida appear to show differences in prey consumption (Barros and Odell , Barros ) and feeding habits (Barros and Odell ) between the sexes.…”
Section: Discussionmentioning
confidence: 99%